Genetic diversity and population structure of an African yam bean (Sphenostylis stenocarpa) collection from IITA GenBank - Shitta, N.S.; Unachukwu, N.; Edemodu, A.; Abebe, A.T.; Oselebe, H.O.; Abtew, W.G. (Springer, 2022)
African yam bean, AYB (Sphenostylis stenocarpa), is an underutilized legume of tropical Africa. AYB can boost food and nutritional security in sub-Saharan Africa through its nutrient-rich seeds and tubers. However, inadequate information on germplasm with desirable agro-morphological traits, including insufficient data at the genomic level, has prevented the full exploitation of its food and breeding potentials. Notably, assessing the genetic diversity and population structure in a species is a prerequisite for improvement and eventual successful exploitation. The present study evaluated the population structure and genetic diversity of 169 accessions from the International Institute of Tropical Agriculture (IITA) collection using 26 phenotypic characters and 1789 single nucleotide polymorphism (SNP) markers. The phenotypic traits and SNP markers revealed their usefulness in uniquely distinguishing each AYB accession. The hierarchical cluster of phenotypes grouped accessions into three sub-populations; SNPs analysis also clustered the accessions into three sub-populations. The genetic differentiation (FST) among the three sub-populations was sufficiently high (0.14–0.39) and significant at P = 0.001. The combined analysis revealed three sub-populations; accessions in sub-population 1 were high yielding, members in sub-population 2 showed high polymorphic loci and heterozygosity. This study provides essential information for the breeding and genetic improvement of AYB.